SELECTION OF INORGANIC FILLERS FOR NONTIRE RUBBER COMPOUNDING - DEMIRHAN, E; DINCER, S; SARAC, HI (MARCEL DEKKER INC, 1994)
Besides tire production, natural and synthetic rubber in vulcanized form are used to prepare various rubber goods such as mechanical goods, hoses, soles, linings to avoid corrosion in chemical processes, gaskets, etc. In the vulcanization of rubber, carbon black and other ingredients are used in the compounding recipes as well as sulfur. Carbon black gives strength to the vulcanized rubber, but carbon black is an expensive filler. Therefore other fillers partially replacing carbon black are also used in the vulcanization processes to reduce the cost of rubber products while maintaining their desired properties. In our work, inorganic fillers, to be used instead of or together with carbon black, were investigated and selection criteria were developed.
Keywords: Polymer Science